2020
DOI: 10.1111/sum.12627
|View full text |Cite
|
Sign up to set email alerts
|

The role of women empowerment and labour dependency on adoption of integrated soil fertility management in Malawi

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
1
6
1
Order By: Relevance
“…Similar findings of gendered social capital on fertilisation were made by Njuki et al (2008), who found that when husbands value and consider the contribution of women to decision making, the household's likelihood to purchase and use inorganic fertilizer increases. The positive influence on manuring however is in sharp contrast to earlier studies that found women in disfavour of manure because its labour requirements are not in sync with household chores (Mponela et al 2020).…”
Section: Isfm Adoptioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar findings of gendered social capital on fertilisation were made by Njuki et al (2008), who found that when husbands value and consider the contribution of women to decision making, the household's likelihood to purchase and use inorganic fertilizer increases. The positive influence on manuring however is in sharp contrast to earlier studies that found women in disfavour of manure because its labour requirements are not in sync with household chores (Mponela et al 2020).…”
Section: Isfm Adoptioncontrasting
confidence: 99%
“…A similar study in southern Africa found that labour constraints affect the adoption of inorganic fertilizer, FYM and residues as a component combination (Mponela et al 2016). The increasing number of children and old household members that the adult worker must look after has been found to put enormous pressure on them, affecting the adoption of labour demanding technologies such as SWC in east and southern Africa (Mponela et al 2020). Apart from addressing gender and youth inclusivity, the ISFM technologies must reduce drudgery as youth dependency ratios are still high in sub-Saharan Africa (UN 2020).…”
Section: Isfm Adoptionmentioning
confidence: 99%
“…This dependency burden on investment is consistent with a similar study in Ghana who found that households with a high dependency ratio made significantly fewer investments in water management than adopters [36]. The extending strategy can regulate dependency ratio forming households with greater productive capacity, due to larger labor forces, and hence the potential for superior economic performance and family household composition is described as a concomitant of application of extending strategies [37].…”
Section: Socio-economic Characteristics and Cultivation Patternsupporting
confidence: 86%
“…Bernier et al (2015) found that women are much less informed than men about climate-smart practices in Kenya, and this affects their ability to invest in such practices; when they are informed, they adopt practices at the same rates as men. Mponela et al (2021) found a more nuanced relationship depending on the NRM practice. A positive relationship was found between women's empowerment (participation in decision-making domains) and adoption of legumes, a negative relationship with manure, and a statistically insignificant relationship with mineral fertilizer.…”
Section: Constraints and Benefits Are Different For Men And Womenmentioning
confidence: 96%